2018
DOI: 10.1111/apt.14528
|View full text |Cite
|
Sign up to set email alerts
|

Symptom association probability does not reliably distinguish functional heartburn from reflux hypersensitivity

Abstract: SummaryBackground: Symptom association probability (SAP) is thought to distinguish reflux

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
14
0
2
Order By: Relevance
“…The same study also found that around 70% of patients who are refractory to PPIs have a reflux rate of <10% (37). A more recent study by Choski et al included a sub-group of patients with heartburn or regurgitation as their chief, PPI-refractory symptom (38). In this study, the difference between patients diagnosed with acid reflux hypersensitivity and those diagnosed with functional heartburn, in terms of the number of symptoms associated with reflux, equated to only 1‒2 pressings per day of the symptom reporting button (38).…”
Section: Diagnosis Of Reflux Hypersensitivity and Functional Heartburnmentioning
confidence: 99%
See 2 more Smart Citations
“…The same study also found that around 70% of patients who are refractory to PPIs have a reflux rate of <10% (37). A more recent study by Choski et al included a sub-group of patients with heartburn or regurgitation as their chief, PPI-refractory symptom (38). In this study, the difference between patients diagnosed with acid reflux hypersensitivity and those diagnosed with functional heartburn, in terms of the number of symptoms associated with reflux, equated to only 1‒2 pressings per day of the symptom reporting button (38).…”
Section: Diagnosis Of Reflux Hypersensitivity and Functional Heartburnmentioning
confidence: 99%
“…A more recent study by Choski et al included a sub-group of patients with heartburn or regurgitation as their chief, PPI-refractory symptom (38). In this study, the difference between patients diagnosed with acid reflux hypersensitivity and those diagnosed with functional heartburn, in terms of the number of symptoms associated with reflux, equated to only 1‒2 pressings per day of the symptom reporting button (38). The authors did not include nonacid reflux in their assessments, pointing out that this increases the probability of chance associations between symptoms and reflux episodes (38).…”
Section: Diagnosis Of Reflux Hypersensitivity and Functional Heartburnmentioning
confidence: 99%
See 1 more Smart Citation
“…While SIs have been used for decades and treatment was provided accordingly, a few investigators have pointed out to some of their limitations and questioned their sensitivity. However, SIs are the best tool we have to identify the patients who are highly sensitive to physiologic amounts of reflux 27 .…”
Section: Diagnosismentioning
confidence: 99%
“…4 In this issue of The Journal, Choki et al question the validity of this expanded usage, especially if used as an indication for anti-reflux surgery. 5…”
mentioning
confidence: 99%